Conway's Game of Life in Quantum-dot Cellular Automata. (March 2021) - Liolis, Orestis; Sirakoulis, Georgios Ch.; Adamatzky, Andrew
Abstract: Quantum-dot Cellular Automata ( QCA ) technology has been considered as one promising solution to deal with the beyond Moore's law and after von Neumann's computing architecture issues, bringing advantages such as high performance and low energy consumption. In this paper, we focus on the implementation in QCA technology of one of the most well-known Cellular Automaton (CA), namely the Game of Life (GoL). GoL introduced by John Conway is one of the most interesting CA, due to the abilities of self-production and computational universality. In this work, a novel fault-tolerant implementation of GoL in programmable crossbar architecture is proposed delivering the computation universality of the GoL in a plausible way. For the provided design, fault-tolerant majority and inverter gates are also presented in a programmable crossbar architecture. Such an implementation provides the QCA circuits designers with an almost endless library of ready-to-use applications, in various scientific fields. Extensive performance evaluation coupled with appropriate simulation results validate the efficacy of the proposed QCA design depicting appropriately the inherent complexity of the GoL rules and structures.